Efeitos dos fruto-oligossacarídeos no pré-tratamento e tratamento total sobre a mucosite intestinal, induzida por 5-fluorouracil - Paula Lopes Armond Carvalho (2019)
The use of the antimetabolic 5-fluorouracil (5-FU) in the cancer treatment leads to the development of side effects such as mucositis. This debility the patient nutritional status and hinders the treatment process. Studies have shown beneficial effects of the use of prebiotic fruit-oligosaccharides (FOS) in inflammatory bowel diseases. FOS contributes to intestinal homeostasis and can mitigate inflammation caused by mucositis. The objective of the present work was to validate the effects of pre-treatment and total treatment with FOS in intestinal mucositis induced by 5-FU investigating possible mechanisms involved in the effect of this prebiotic. BALB/c male mice were used, they were divided into 5 groups: control (without mucositis + saline solution), FOS (without mucositis + 6% FOS), MUC (with mucositis + saline solution), PT(with mucositis + 6% FOS supplementation before disease induction) and TT(with mucositis + 6% FOS supplementation during the entire experimental period).The animals were fed with a commercial diet and supplemented with FOS or saline via gavage for 10 days. Mucositis was induced with a single intraperitoneal injection (300 mg/kg) of 5-FU on the seventh day. After 72 hours of injection, the mice were anesthetized and euthanized, and the material was collected for the analyses. Before the induction of mucositis, no changes in food intake and weight variation were observed in all groups (p > 0,05). However, after the induction of mucositis a reduction of both parameters were observed for the MUC group (p < 0,05) and the supplementation with FOS was not able to prevent the reduction in consumption and weight loss. The animals that received FOS showed physiological levels of intestinal permeability (IP) in both treatments. The PT and TT groups showed a reduction in bacterial translocation (BT) in relation to the MUC group (p < 0,05). The results of IP and BT are in agreement with the histological data that showed partial preservation of the intestinal architecture in the ileum with maintenance of the villi height and depth of the crypts in the animals that received the pretreatment and total treatment. The analysis of the tight junctions showed that the two modalities of treatment were able to preserve the production of this protein also preventing IP and BT. There was an increase in the activities of MPO and EPO in the MUC group (p < 0,05) in relation to the other groups and both treatments were able to prevent the inflammatory infiltrate. The analysis of IL-10 cytokine showed no difference between the groups (p > 0.05) and TNF-α concentration showed a significant reduction in the groups with mucositis (p < 0,05). The supplementation with FOS was able to increase the production of short-chain fatty acids (SCFA), but the animals with mucositis that received the treatments presented levels of acetate and butyrate similar to the MUC group (p > 0,05), the propionate concentration in PT and TT groups was similar to the control (p > 0,05). The concentration of sIgA was reduced in the group MUC and TT showed similar levels to CTL (p < 0,05). The total treatment was able to maintain the mucus production similar to the control group, as well as the production of sIgA besides presenting greater preservation of the mucosa in the histological analysis, promoting beneficial effects on the intestinal mucositis showing higher efficacy when compared to pretreatment modalities.